Study of Adsorption of Lead Metal (Pb) Using Chemically Acti-vated (Nypa Fruticans) Powder Biosorbent - Meriatna Meriatna; Lukman Hakim; Masrullita Masrullita; Zulmiardi Zulmiardi; Suri Atika (International Journal of Engineering, Science and Information Technology, 2023)
Heavy metal contamination in the environment is now quite concerning, and it is hazardous if it enters the body. Continuous human interaction with heavy metal lead (Pb) will result in various health problems. Nipa palm is a palm (Palma) thrives in mangrove forest habitats or along the seashore, with a cellulose content of 35.1%, 26.4% hemicellulose, and 17.8% lignin. This research aims to see if palm fronds (Nypa fruticans) can be used as a biosorbent to remove the heavy metal Pb in artificial solutions. The analysis was carried out in phases, beginning with the creation of biosorbents from Nipah fronds by decreasing their size to powder and drying them in the sun, followed by analyzing the efficacy of the biosorbents and the number of functional groups using the FTIR instrument. The research was carried out by varying the particle size of the nipa palm frond adsorbent, namely 40, 60, and 80 mesh, as well as contact times of 30, 60, 90, and 100 minutes, to determine the level of adsorption absorption and the adsorption mechanism using the Langmuir and Freundlich isotherm equation approach. The Pb solution used had a concentration of 20 ppm. The results showed that the maximum metal absorption level was 99.29% at a particle size of 80 mesh with a contact time of 100 minutes. The absorption mechanism is close to the Langmuir isotherm equation with R2 = 0.9998. It is suspected that the adsorption process occurs in one layer (monolayer) of the adsorbent.